4(3z-1)-3(z-8)=3(z-1)

Simple and best practice solution for 4(3z-1)-3(z-8)=3(z-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3z-1)-3(z-8)=3(z-1) equation:


Simplifying
4(3z + -1) + -3(z + -8) = 3(z + -1)

Reorder the terms:
4(-1 + 3z) + -3(z + -8) = 3(z + -1)
(-1 * 4 + 3z * 4) + -3(z + -8) = 3(z + -1)
(-4 + 12z) + -3(z + -8) = 3(z + -1)

Reorder the terms:
-4 + 12z + -3(-8 + z) = 3(z + -1)
-4 + 12z + (-8 * -3 + z * -3) = 3(z + -1)
-4 + 12z + (24 + -3z) = 3(z + -1)

Reorder the terms:
-4 + 24 + 12z + -3z = 3(z + -1)

Combine like terms: -4 + 24 = 20
20 + 12z + -3z = 3(z + -1)

Combine like terms: 12z + -3z = 9z
20 + 9z = 3(z + -1)

Reorder the terms:
20 + 9z = 3(-1 + z)
20 + 9z = (-1 * 3 + z * 3)
20 + 9z = (-3 + 3z)

Solving
20 + 9z = -3 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
20 + 9z + -3z = -3 + 3z + -3z

Combine like terms: 9z + -3z = 6z
20 + 6z = -3 + 3z + -3z

Combine like terms: 3z + -3z = 0
20 + 6z = -3 + 0
20 + 6z = -3

Add '-20' to each side of the equation.
20 + -20 + 6z = -3 + -20

Combine like terms: 20 + -20 = 0
0 + 6z = -3 + -20
6z = -3 + -20

Combine like terms: -3 + -20 = -23
6z = -23

Divide each side by '6'.
z = -3.833333333

Simplifying
z = -3.833333333

See similar equations:

| (T-2)/(4-t) | | -9+10x=4x+15 | | 9=12x^2-23x | | -77.08=9.4y | | 2x-1-4=0 | | -0.56m=4.592 | | 2.3x=14.582 | | 2c+4=14 | | 5/6z-100 | | 13-6m=4-6m | | 3^4/5*3^3/x | | 11k=13t-7k/2t | | 6b^2+48b=0 | | -243=-9(10+n) | | 2x-4-(12+4x)=3x | | 3q^2-6q+2=0 | | 24+3y=24+2x | | x/10=1/4 | | 2x=x*2-15 | | 29x=5x+21+3x | | 4.3x+2=-1 | | A-b-5=p | | S^2-6s+4=0 | | (9m+11)(m+9)=79 | | -7x^2+15x+15=0 | | -8x^2+2x+10=0 | | 277.5-2.5t=555-16t^2 | | ry=x-45 | | 2[w-(2w+19)+14]=2(w+5) | | 10x-11+x^2=0 | | 7x-2(6-x)+2=18 | | (x-2)(x+5)=60 |

Equations solver categories